An Analysis of Indonesian EFL Students' Ability to Interpret English Idioms In Youtube Short Drama - Natasha, Harum (Indonesian Journal of Integrated English Language Teaching, 2023)
Abstract Many studies have discussed the EFL student's abilities in translating idioms into English. However, a few discussed the Indonesian EFL students' ability to interpret English idioms from a short drama scene. An investigation into this is considered significant since English is called an idiom language. Indonesian EFL students need to be able to interpret these English idioms to speak naturally, like a native speaker. Comprehending and using them with ease may indicate language competency, as they may be useful for improving students' communication abilities in everyday situations (Beloussova, 2015).This study intended to determine the ability of Indonesian EFL students to interpret English idioms directly from a short drama conversation. The study participants were in the fifth semester of the English Education Department of the State Islamic University of Sultan Syarif Kasim Riau. The data was taken by asking them to watch the drama to listen to the conversation containing idioms and filling in a Google form to interpret them. Through qualitative data analysis, the researcher followed the five sequential data analyses (Cresswel, 2018). The findings revealed that most Indonesian EFL students are able to interpret English idioms from YouTube short drama conversations. They use the reduction strategy in interpreting English idioms.Keywords: Interpretation, English idioms, Indonesian EFL students